God’s daughters in conflict : an exploration of the use of religious texts in Christian discourse on gender roles - Lee, Jisun (2023)
Feminist scholars and theologians have examined the effects of the dominantly male language in the Bible on the sociopolitical beliefs and attitudes of evangelical Christians on gender roles. However, not much research has been done on Christian discourse, and on how Christian individuals talk regarding said topic. Moreover, I could not find any literature on how Christian individuals use, refer to, and interpret the Bible while in discourse. In my article, I first lay out the history of the role that women have had in Christianity and provide a breadth of scholarship that pertains to my topic. Then, using discourse analysis, I explore how four individuals with different denominational and sociocultural influences use the Bible during my focus group study on the Bible and how it should be read. I add to the field of discourse analysis within Christian studies by emphasizing the agency of the Christian individuals when reading the Bible. I also explore how their discussing a variety of topics.